1988
DOI: 10.3382/ps.0671797
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Irradiation Dose and Temperature Effects on the Sensory Properties of Turkey Frankfurters

Abstract: Effects were studied of gamma irradiation (0, 0.5, 1.0 Mrad) on selected sensory properties of two turkey frankfurter formulations (2.5% NaCl, and 1.5% NaCl + .4% tripolyphosphate) at two irradiation temperatures (2 C and -30 C). In the ten different combinations tested, no significant change in product tenderness was observed. The 2.5%-NaCl-treated nonirradiated frankfurters received higher freshness scores and had less off flavor than the 2.5% irradiated frankfurters. The magnitude of difference was not alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Each of the studies indicated the feasibility of utilizing low dose gamma irradiation (< 5.0 kGy) for the elimination of food-borne pathogens while maintaining acceptable product sensory attributes of the frankfurters. The higher radiation dose of 3.55 kGy required to produce a five log reduction in L. monocytogenes surface inoculated onto Mixed Meat Frankfurter #1 is well below the 5.0 kGy dose used by Barbut et al (1988) to produce organoleptically acceptable turkey frankfurters. The dose of 3.55 kGy is also less than half the radiation dose of 8.0 kGy which produced three undesirable sensory attributes in the beef frankfurters tested by Terrell et al (1981a,b,c.…”
Section: Surface-inoculated Commercially Available Frankfurtersmentioning
confidence: 88%
See 1 more Smart Citation
“…Each of the studies indicated the feasibility of utilizing low dose gamma irradiation (< 5.0 kGy) for the elimination of food-borne pathogens while maintaining acceptable product sensory attributes of the frankfurters. The higher radiation dose of 3.55 kGy required to produce a five log reduction in L. monocytogenes surface inoculated onto Mixed Meat Frankfurter #1 is well below the 5.0 kGy dose used by Barbut et al (1988) to produce organoleptically acceptable turkey frankfurters. The dose of 3.55 kGy is also less than half the radiation dose of 8.0 kGy which produced three undesirable sensory attributes in the beef frankfurters tested by Terrell et al (1981a,b,c.…”
Section: Surface-inoculated Commercially Available Frankfurtersmentioning
confidence: 88%
“…In those studes a radiation dose of 8.0 kGy produced undesirable sensory traits in 3 of 18 categories while frankfurters irradiated at a dose of 32 kGy were scored as being less palatable in 8 of 18 categories (Terrell et al 1981a,b,c). Sensory studies conducted with vacuum packaged turkey frankfurters irradiated to doses of 0,5.0, and 10.0 kGy, at temperatures of 2C and -3OC, indicated it was possible to obtain product which was not significantly different than nonirradiated frankfurters (Barbut et al 1988). Each of the studies indicated the feasibility of utilizing low dose gamma irradiation (< 5.0 kGy) for the elimination of food-borne pathogens while maintaining acceptable product sensory attributes of the frankfurters.…”
Section: Surface-inoculated Commercially Available Frankfurtersmentioning
confidence: 97%
“…When beef and pork frankfurters were irradiated at doses of 8 and 32 kGy (irradiation temperature: -34°C), an off-odor and off-flavor were noticed, and the intensity of the off odor increased with radiation dose (3). Frankfurters irradiated at 5 and 10 kGy were often scored higher in off-flavor than the non-irradiated ones (4). However, ready-to-eat beef luncheon meats irradiated at doses of 2-4 kGy had similar off-flavor as the non-irradiated controls (5).…”
mentioning
confidence: 99%